Faktor yang Berhubungan dengan Kelelahan Kerja pada Karyawan Bagian Penggorengan di Pabrik Abon Vivi Kefamenanu Kabupaten Timor Tengah Utara - Rizkiyah Ramadhani; Luh Putu Ruliati; Johny A. R. Salmun (Media Kesehatan Masyarakat, 2021)
Meat floss production requires time as it involves a heavy workload. In addition, poor posture and work environment may cause fatigue and workplace accidents for the workers. There are two causes of fatigue, physical fatigue which is due to work-related environment factors and non-physical fatigue which is due to individual factors. Fatigue can affect health and work performance leading to productivity loss and accidents. This research aims to determine factors associated with work fatigue of workers at the Vivi Meat Floss Factory in Kefamenanu. This research was analytic with a cross-sectional design. The population in this study consisted of all workers (32 women) at the factory. A total sampling technique was applied to select the sample. The data were analyzed using logistic regression. The results showed that the factors related to work fatigue were job tenure period (p-value of 0.001 < 0.05), age (p-value of 0.002 < 0.05), work posture (p-value of 0.002 < 0.05), duration (p-value of 0.006 < 0.05), and temperature (p-value of 0.002 < 0.05).